Formación mental y crisis mundial (El hombre y sus ideas) - Wallas, Graham (CIC. Cuadernos de Información y Comunicación, 2005)
The author exposes for the first time his theory of incubation in creativity, in which it is essential the rest and pause of all mental conscious activity to achieve the best results. Incubation phase, after an information period, is essential to attain creative results in all types of activity, as the author shows thought examples and experiences. This text has incalculable value for its date and the true modernity of the ideas that are displayed in it.
Keywords: incubation; creativity; education; learning; experiences and examples in creative incubation